Ethanol-promoted fabrication of tungsten oxide nanobelts with defined crystal orientation - Suphaporn Daothong (2018)
A controlled method for the production of tungsten oxide nanobelts through metal oxidation in presence of ethanol is proposed. At the optimal synthesis conditions, up to 20 μm long vertically aligned ribbon-like structures with a narrow rectangular cross section can be obtained in a tuned manner with preferential formation of WO2in the presence of graphitic like carbon. Bulk and local-scale studies suggest that carbon diffusion to the surface of the material leads to the formation of mainly WO3nanobelts from simple annealing treatments at 450 °C. This represents one alternative method to the common tungsten oxidation in air, opening the possibility to use C-containing compounds with negligible formation of carbide traces. An in-depth characterization of these materials has been performed, and the possible growth mechanisms are here discussed. © 2010 American Chemical Society.